Movement disorders associated with acetylcholinesterase inhibitors in Alzheimer’s dementia: A systematic review - Jamir Pitton Rissardo; Ana Letícia Fornari Caprara (Brain Circulation)
BACKGROUND: Acetylcholinesterase inhibitors (AChEIs) are widely used in Alzheimer’s disease (AD). This study aims to systematically review the literature about movement disorders (MDs) associated with AChEIs for AD, which include donepezil, galantamine, rivastigmine, tacrine, and ipidacrine. METHODOLOGY: Two reviewers conducted a comprehensive review of relevant studies across six databases, without language restrictions, covering publications from 1992 to 2024. RESULTS: Overall, 74 studies containing 92 cases were found of MDs related to ACHEIs. The MDs found were Pisa syndrome in 33 patients, parkinsonism in 31, myoclonus in 11, dystonia in 10, dyskinesia in 6, and extrapyramidal symptoms in 1. Regarding the medications, the abnormal movements were associated with donepezil in 62 cases, rivastigmine in 15, galantamine in 10, and tacrine in 5. No case of ipidacrine-induced MD was found. Overall, the most commonly affected sex was the female, accounting for 61.9% of the cases. The mean and median age was 74.1 (standard deviation: 8.9) and 75 years (range: 49–93 years). The MD occurred within 6 months of the starting of AChEI in approximately 70% of the patients. Furthermore, the full recovery of the MD after the main management was noticed within 6 months in about 80% of the patients. About 86.3% of the individuals fully recovered after treatment, which included AChEI discontinuation, dose adjustment, and prescription of additional therapy. CONCLUSIONS: The occurrence of tacrine-induced tremor indicated a potential predisposition to movement disorders associated with AChEI therapy. Based on the drug class side effect profile, it is possible that future studies may observe abnormal movements with other AChEIs.